Great Moderation(s) and U.S. Interest Rates: Unconditional Evidence - James M. Nason; Gregor W. Smith (Queen's University, Department of Economics, 2007)
The US economy experienced a Great Moderation sometime in the mid-1980s – a fall in the volatility of output growth – at the same time as a fall in both the volatility of inflation and the average rate of inflation. We put this moderation in historical perspective by comparing it to the post-WWII moderation. According to theory, the statistical moments – both real and nominal – that shift during these moderations in turn influence interest rates. We examine the predictions for shifts in the unconditional average of US interest rates. A central finding is that such shifts probably were due to changes in average inflation rather than to those in the variances of inflation and consumption growth.
Keywords: E32; E43; N12; 330; great moderation; asset pricing